Pentahelix Stakeholder Synergy in a Public Communication Perspective to Realize Digital Tourism - Helmi, Rahmadhona Fitri; Nurhabibi, Pratiwi; Evelynd, Evelynd; Putri, Sinta Westika; Ikhlas, Al (Faculty of Social Science, Universitas Negeri Padang, 2024)
The tourism industry in Indonesia was the second-largest contributor to foreign exchange earnings, which absorbed approximately 10% (13 million workers) of the total national workforce in 2019. However, COVID-19 led to a drastic decline in tourists visiting Indonesia. The number of tourists in West Sumatra Province decreased by more than 50%, while the city of Padang experienced a decrease of more than 75% for foreign and 50% for domestic tourists. To solve this problem, the Padang City Tourism Office devised an alternative solution using digital platforms. The Padang City Tourism Office launched an application called SIDETA (Tourist Destination Information System), which contains information about tourism in Padang. This research aims to investigate how the collaboration between the Padang City Tourism Office and other helix elements contributes to the realization of digital tourism in Padang City and analyze the obstacles and challenges faced by the Padang City Tourism Office in building synergy with other helix elements. This research uses a qualitative and quantitative research approach. Informants and respondents were selected using purposive sampling. Furthermore, three data collection techniques were used: surveys, rapid appraisal, and participatory methods. The results show that 75% of the helix elements in Padang's tourism sector are unaware of the existence of the SIDETA, and 94.2% admit to not being involved in the creation and development of the application.